2016
DOI: 10.1089/jamp.2015.1255
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Fluticasone Propionate/Formoterol Fumarate Combination Therapy Is Associated with a Low Incidence of Severe Asthma Exacerbations

Abstract: Background: A primary goal of asthma management is the reduction of exacerbation risk. We assessed the occurrence of oral corticosteroid-requiring exacerbations (OCS exacerbations) with long-term fluticasone/formoterol therapy, and compared it with the occurrence of similar events reported with other inhaled corticosteroid/long acting β2-agonist (ICS/LABA) combinations.Methods: The occurrence of OCS exacerbations was assessed in two open-label trials of fixed-dose fluticasone/formoterol administered for betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 98 publications
5
36
0
Order By: Relevance
“…It is also notable that there were no severe exacerbations (requiring oral or parenteral steroid use, emergency treatment or hospitalization) in either treatment arm in the core phase or with FP/FORM throughout the extension phase in the current study. This is in line with findings from a previous analysis that assessed the occurrence of severe exacerbations (requiring oral corticosteroids) during two long-term studies with FP/FORM compared with data for other ICS/LABA combinations from published Cochrane analyses [Papi et al 2013;Lasserson et al 2008;Ducharme et al 2010]. A low incidence of corticosteroid-requiring exacerbations was observed during 6-12 months of treatment with FP/FORM in this pooled analysis among a total of 752 patients aged 12 years and above which compared favourably with the incidence observed in long-term studies with single-inhaler FP/SAL and budesonide/formoterol, and with free combinations of individual ICS and LABA formulations [Papi et al 2013].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is also notable that there were no severe exacerbations (requiring oral or parenteral steroid use, emergency treatment or hospitalization) in either treatment arm in the core phase or with FP/FORM throughout the extension phase in the current study. This is in line with findings from a previous analysis that assessed the occurrence of severe exacerbations (requiring oral corticosteroids) during two long-term studies with FP/FORM compared with data for other ICS/LABA combinations from published Cochrane analyses [Papi et al 2013;Lasserson et al 2008;Ducharme et al 2010]. A low incidence of corticosteroid-requiring exacerbations was observed during 6-12 months of treatment with FP/FORM in this pooled analysis among a total of 752 patients aged 12 years and above which compared favourably with the incidence observed in long-term studies with single-inhaler FP/SAL and budesonide/formoterol, and with free combinations of individual ICS and LABA formulations [Papi et al 2013].…”
Section: Discussionsupporting
confidence: 90%
“…As expected based on previous data from adolescents and adults [Papi et al 2013[Papi et al , 2015, a low number of patients experienced asthma exacerbations during either FP/FORM or FP/SAL treatment in the core trial [4 (3.8%) FP/FORM patients and 3 (2.9%) FP/SAL patients]. This finding supports data from the previous pooled analysis of studies with FP/FORM in patients aged 12 years and over that showed a lower incidence of any exacerbation type compared with FP monotherapy [Papi et al 2015].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus we consider the reduction in short-term exacerbation risk (all severities) to be [33]. Longer term non-comparative studies with fluticasone/formoterol also suggest that it is likely to be an effective long-term treatment to reduce exacerbation risk; in two separate studies in which patients were treated for 6e12 months and 14 months, respectively, the incidence of oral corticosteroid-requiring exacerbations was only 2.3% and 1.8%, respectively [34]. A direct comparison of the treatment effects seen in this pooled analysis versus those from previous landmark ICS/ LABA studies of budesonide/formoterol and fluticasone/ salmeterol such as FACET [35] and GOAL [36] is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Flutiform ® (FP/FORM) is an inhaler product containing a combination of fluticasone propionate (FP) and formoterol fumarate (FORM), approved for maintenance use in asthma following a comprehensive series of studies [1][2][3][4][5][6][7][8][9][10]. It is currently available within a conventional hydrofluoroalkane-propelled pressurised metered-dose inhaler (pMDI).…”
Section: Introductionmentioning
confidence: 99%